Kepemimpinan Kepala Madrasah Dalam Meningkatkan Sikap Disiplin Guru Di MTS Swasta Nurussholih Medan Polonia - Citra Malinda Sitorus; Afrahul Fadhilla Daulai; Fachruddin Azmi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The progress of a nation cannot be separated from the progress of the world of education. According to Law Number 20 of 2003 concerning the National Education System, article 1 paragraph (1) states that